Informacyjne zarządzanie potencjałem pracowniczym w przedsiębiorstwie - Łapińska, Anna; Grzebski, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this work is to present benefits resulting from implementation of personnel remuneration module (HR). One of the best and most widespread integrated information syster R/3 system of SAP AG company. Full description of functioning rules of R/3 system enable present the importance of the implementation of that system to a company. The work presents HR a module and methods of its implementation used by SAP. ANWIL company's organization and terms of functioning are also shown here. Human Resources Remuneration departments are described. Moreover, it presents benefits resulting from implementation of this system into the company in perspective of 3 years. The aim of this paper w; verify the need of making use of such a system and its benefits. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 197-211